Firmino Costa: The Republic of an intellectual and educational purpose (1907 - 1937) - Cesário Hamdan, Juliana (Revista Historia de la Educación Latinoamericana, 2014)
The purpose of this article is to analyse the performance of Firmino Costa an educator from Minas Gerais State, by taking historical feedebacks which are on the basis of ways and means of his political and intelectual roles. We have, for this analisys, looked over the works of Alonso 2008, of Oliveira 1999 and Carvalho 2003, by considering they bring up relevant contributions for the understanding of the histories of vivid ideas present between precedent years and the first decades of the Republic Proclaimation. The three works eventhough as of distinct objects and objectives, reject interpretation that, on one aspect, deal with the intelectual Republic ambience by means of intelectual tipologies clivages which would have been passively absorving european and american theories and, on the other hand, the ones that are stressed by studies that approach individual actions commited to the holding on ahead its ideological collors. These authors, on the contrary, understand that individuals are involved in determined cultural ambiences built up from sociability nets and by the running ideas repertory and, as to this very circusntance, they have different political and intelectual ways of acting by in a large scale, conditioning these factors to the possibilities of acting. So in this article the effort is trying to fix connectives amomg some elements of cultural ambience within the previous years to the Republic and relating them to the political and intelectual ways of acting that have enabled the educational information for the educator from Minas Gerais State. This analitycal movement, by itself had demanded that we should have resorted to some of the theoretical formulations of Antonio Gramsci 1975 as to the action senses of the intellectuals, as means of understanding them from the context and as the possibilities of acting are concerned, that have enabled the educator from Minas the achieving of their intents.